Landscape structure shapes the diversity of beneficial insects in coffee producing landscapes. (October 2019) - Medeiros, Hugo Reis; Martello, Felipe; Almeida, Eduardo A.B.; Mengual, Ximo; Harper, Karen A.; Grandinete, Yuri Campanholo; Metzger, Jean Paul; Righi, Ciro Abbud; Ribeiro, Milton Cezar
Abstract: The expansion of monocultures and the overuse of agrochemicals have resulted in the loss of beneficial insects and disruption of ecosystem services such as pollination and biological control in agricultural landscapes. Bees, wasps and flower flies were our model groups to investigate how landscape structure attributes affect alpha and beta diversity of different beneficial insect groups in Brazilian landscapes containing coffee crops. Species richness and abundance of wasps, and bee richness were positively correlated with forest cover at multiple spatial extents. Bee abundance, and species richness and abundance of flower flies did not respond to any landscape predictor. The community composition of wasps and bees in landscapes with low forest cover was composed of subsets of the communities located in forested landscapes, leading to species loss in structurally impoverished landscapes. High variations in landscape diversity and edge density between landscapes resulted in flower fly species replacement suggesting that pairs of landscapes with high and low diversity of habitat types and edge density harbor different species. Such results indicate that initiatives for the conservation of beneficial insects in the Atlantic Forest biodiversity hotspot must focus on forest conservation and restoration, because high levels of forest loss can result in the loss of wasp and bee species with potential negative consequences for the provision of pollination and pest control services in agroecosystems. Our findings can aid conservationists and policy makers to define priority actions for biodiversity conservation as well as the selection of appropriate spatial scales in landscape planning and management. Highlights: Landscape structure moderates species compositions of beneficial insects in farmland. Forest loss in the surrounding landscape resulted in wasp and bee species loss. Variations in landscape structure resulted in flower fly species turnover. Biodiversity conservation practices must focus on forest conservation and restoration.